Understanding cumulative risk - BYRNE, RUTH MARY JOSEPHINE (My University, 2010)
The authors investigated the relationship between reasoners' understanding of subjunctive conditionals (e.g., if p had happened, then q would have happened) and the inferences they were prepared to endorse. Reasoners who made a counterfactual interpretation of subjunctive statements (i.e., they judged the statement to imply that p and q did not happen) endorsed different inferences than those who did not. Those who made a counterfactual interpretation were more likely to (a) judge the situation in which p and q occurred to be inconsistent with the conditional statement and (b) make negative inferences such as modus tollens (i.e., approximately q therefore approximately p). These findings occurred with familiar and unfamiliar content, affirmative and negative conditionals, and conditional and biconditional relations.
PUBLISHED
Keywords: Risk judgments; Decision making; Psychology